2012
DOI: 10.1108/17511061211238939
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender on wine purchasing and consumption

Abstract: Purpose -The purpose of this paper is to investigate the purchasing behaviour of consumers across four nations and evaluate the influence that gender has on wine purchasing decisions. Design/methodology/approach -An interviewer-administered questionnaire was used to examine the actual purchase decisions made by 399 consumers inside stores in New Zealand, Australia, the UK and the USA. Findings -The results indicate that gender has little significant impact on the frequency with which consumers purchase and dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 36 publications
4
37
0
1
Order By: Relevance
“…Barber et al (2008a) found that subjective wine knowledge is more closely related to past wine experience and consumption than it is to actual wine knowledge. Subjective wine knowledge has been found to be significantly higher amongst Generation X respondents than Millennials (Barber et al, 2008a) and amongst males than females (Barber et al, 2008b;Bruwer and Johnson, 2010;Forbes, 2012).…”
Section: Subjective and Objective Knowledgementioning
confidence: 96%
“…Barber et al (2008a) found that subjective wine knowledge is more closely related to past wine experience and consumption than it is to actual wine knowledge. Subjective wine knowledge has been found to be significantly higher amongst Generation X respondents than Millennials (Barber et al, 2008a) and amongst males than females (Barber et al, 2008b;Bruwer and Johnson, 2010;Forbes, 2012).…”
Section: Subjective and Objective Knowledgementioning
confidence: 96%
“…Consequently, a lot of research on wine consumers' purchase decision deals with the importance of individual consumer characteristics like product involvement (Forbes, 2012). Previous studies have shown that involvement impacts the product attributes which consumers choose to evaluate a wine (Bruwer and Huang, 2012;Barber et al, 2008a;Quester and Smart, 1996;Zaichkowsky, 1985) and that it can be used to segment the wine market (Lockshin et al, 1997(Lockshin et al, , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that involvement impacts the product attributes which consumers choose to evaluate a wine (Bruwer and Huang, 2012;Barber et al, 2008a;Quester and Smart, 1996;Zaichkowsky, 1985) and that it can be used to segment the wine market (Lockshin et al, 1997(Lockshin et al, , 2001). Moreover, international research has shown that demographic variables such as gender (Forbes, 2012;Barber et al, 2006) or age (Fountain and Lamb, 2011;Thomas and Pickering, 2005;Goldsmith and d'Hauteville, 1998) affect the wine purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, Atkin, et al (2007) aplicaron un cuestionario a 1374 consumidores de vino en Estados Unidos (497 hombres y 877 mujeres), encontrando que las etiquetas son significativamente más importantes para las mujeres y que si bien la región vitivinícola es muy relevante para ambos géneros, las mujeres se fijan más en las medallas y premios del producto. Forbes (2012), por su parte, encontró que el género influye significativamente en la utilización por parte del consumidor de vino de la aplicación de precio de descuentos y la referencia de la región de origen. Atkin y Sutanonpaiboon (2007) realizaron un estudio multinacional sobre las preferencias de vino según género, detectando que el patrón de preferencias de género de los consumidores de vino en esos países era bastante constante, lo que indicaba que el género era una base sobresaliente para segmentar el mercado del vino.…”
Section: Antecedentes Teóricosunclassified